José María Gabriel y Galán Moris (1968-2020) pteridólogo - Salvo Tierra, Ángel Enrique; Molino de MIguel, Sonia (Acta Botanica Malacitana, 2020)
Nota necrológica de nuestro compañero José María Gabriel y Galán Moris.